Compression and tension forces in bamboo truss with curved model - Khalil, Omar Khaled Farouk Ahmed; Prihatmaji, Yulianto Purwono (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Enhancing the strength performance of bamboo truss. This paper discusses the performance of a customize bamboo truss and emphasizing how stress forces interact under vertical loads. The customize truss with a span 4 meters and a height with 2 meters, comprises three components; the base, truss legs and bracing. At the base of the truss underneath, whole bamboo is utilized. In contrast, the bracing section employs curved stacks of split bamboo. The design variation allows for structural support while incorporating the flexibility and strength of bamboo in different parts of the truss. It’s essential to ensure the structural integrity and load-bearing capacity in bamboo trusses. The aim of this study to investigate how the customize truss respond to the stress forces, focusing on the ability to withstand vertical loads. This research collecting data by using a quantitative methods after customizing a unique model of bamboo truss with curved stacks then conducting an experiment under hydraulic test. As a result the curved stacks model in the customize truss successes to withstand 4.78 KN vertical load.